2009
DOI: 10.1073/pnas.0810961106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical networks in tRNA:protein complexes

Abstract: Community network analysis derived from molecular dynamics simulations is used to identify and compare the signaling pathways in a bacterial glutamyl-tRNA synthetase (GluRS):tRNA Glu and an archaeal leucyl-tRNA synthetase (LeuRS):tRNA Leu complex. Although the 2 class I synthetases have remarkably different interactions with their cognate tRNAs, the allosteric networks for charging tRNA with the correct amino acid display considerable similarities. A dynamic contact map defines the edges connecting nodes (amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
1,122
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 738 publications
(1,133 citation statements)
references
References 30 publications
11
1,122
0
Order By: Relevance
“…Global reorientation and intradomain configurational dynamics of TM4 are strongly coupled to both the global and intradomain dynamics of TM5. The importance of several of the most highly cross-correlated TM residues in these regions was previously characterized in an NMR study, which found that backbone dynamics of Tyr358 and Gln359 are correlated with anticoagulant activity and that backbone dynamics of Tyr413 and Ile414 are inversely correlated with thrombin binding (24). This tight coupling between TM4 and TM5 was previously shown experimentally to depend on M388 in the TM4-TM5 linker (25,26).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Global reorientation and intradomain configurational dynamics of TM4 are strongly coupled to both the global and intradomain dynamics of TM5. The importance of several of the most highly cross-correlated TM residues in these regions was previously characterized in an NMR study, which found that backbone dynamics of Tyr358 and Gln359 are correlated with anticoagulant activity and that backbone dynamics of Tyr413 and Ile414 are inversely correlated with thrombin binding (24). This tight coupling between TM4 and TM5 was previously shown experimentally to depend on M388 in the TM4-TM5 linker (25,26).…”
Section: Discussionmentioning
confidence: 84%
“…Allosteric networks were characterized using a community network analysis approach previously applied to investigate allostery in tRNA-protein complexes and other protein systems (24,31,32). This approach constructs a dynamic contact map consisting of a network graph in which each residue is treated as a "node" connected by edges to other nodes when two residues are deemed to be "in contact."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Community analysis can also be applied to correlated motions in proteins and nucleic acids (18,19). In such studies, MD simulations are performed and correlations among residues are evaluated.…”
mentioning
confidence: 99%
“…Community analysis of such correlation networks identifies relatively independent communities of residues that behave as semirigid bodies. Initial applications of this method to study protein dynamics provided insight into the propagation of allosteric signals in bacterial tRNA-synthetases (18) and in a sortase enzyme from Staphylococcus aureus (19).…”
mentioning
confidence: 99%